2008
DOI: 10.1075/silv.2.22szm
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic determinants of genitive variation in spoken and written English: A multivariate comparison across time, space, and genres

Abstract: Probabilistic Determinants of genitive variation in spoken and written English: a multivariate comparison across time, space, and genres ABSTRACT. This is a paper about language variation and about language change, investigating the competition between the s-genitive and the of-genitive in Modern English (written and spoken, British and American) as a case study. Drawing on a range of spoken and written corpora and considering a multivariate envelope of seven major conditioning factors (such as possessor anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
49
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 13 publications
10
49
1
1
Order By: Relevance
“…We will not speculate as to why our results are different from Hundt and Szmrecsanyi (2012) except to note that their study examined data of a different time period (late 19th and early 20th century) and medium (written) from ours. Next, we saw earlier that previous studies comparing AmE to BrE have reported a number of probabilistic contrasts, such as inanimate possessors discouraging s-genitive usage less strongly in AmE than in BrE, and/or animate possessor more strongly favoring the s-genitive in BrE than in AmE (Jahr Sohrheim 1980; Hinrichs & Szmrecsanyi 2007;Szmrecsanyi & Hinrichs 2008;Szmrecsanyi et al 2014). The previous literature also suggests that in the written medium at least, long possessums favor s-genitive usage in AmE but not in BrE (Hinrichs & Szmrecsanyi 2007).…”
Section: Genitive Variation: Interim Summarymentioning
confidence: 79%
“…We will not speculate as to why our results are different from Hundt and Szmrecsanyi (2012) except to note that their study examined data of a different time period (late 19th and early 20th century) and medium (written) from ours. Next, we saw earlier that previous studies comparing AmE to BrE have reported a number of probabilistic contrasts, such as inanimate possessors discouraging s-genitive usage less strongly in AmE than in BrE, and/or animate possessor more strongly favoring the s-genitive in BrE than in AmE (Jahr Sohrheim 1980; Hinrichs & Szmrecsanyi 2007;Szmrecsanyi & Hinrichs 2008;Szmrecsanyi et al 2014). The previous literature also suggests that in the written medium at least, long possessums favor s-genitive usage in AmE but not in BrE (Hinrichs & Szmrecsanyi 2007).…”
Section: Genitive Variation: Interim Summarymentioning
confidence: 79%
“…The Early Modern English period, however, sees a revival of the s-genitive, "against all odds" (Rosenbach 2002: 184). In Present-Day English, the s-genitive is comparatively frequent (Rosenbach 2002, Hinrichs & Szmrecsanyi 2007, Szmrecsanyi & Hinrichs 2008), and appears now to be spreading (Potter 1969, Dahl 1971, Raab-Fischer 1995, Rosenbach 2003, Szmrecsanyi 2009). In the news genre specifically, Hinrichs & Szmrecsanyi (2007) diagnose a spread of the s-genitive in late twentieth-century press English which appears to be due to a process of 'economization' .…”
Section: A Very Short History Of Genitive and Dative Variation In Engmentioning
confidence: 97%
“…Leech et al 2009) have further shown that the two variables take part in different kinds of stylistic change. The progressive, for instance, is a construction that has been discussed in the context of the ongoing colloquialisation of written language in BrE and AmE (Leech et al 2009: 239), whereas the shift towards s-genitives contributes to the densification, or "eco-nomization" (Hinrichs and Szmrecsanyi 2007;Szmrecsanyi and Hinrichs 2008), of content observed in some written genres (Leech et al 2009: 250). Both trends are apparent in 20th-century newspaper writing, whereas a text type like personal letters is unlikely to be affected by densification.…”
Section: Progressives and Genitives: An Interim Discussionmentioning
confidence: 99%